Influence of Classroom Ergonomics on Students' Academic Productivity and Emotional Disposition - Ibanez, Mercedes (12th International Scholars Conference 2025, 2026)
The ergonomic design of learning plays a vital role in ensuring students' comfort, safety, and educational engagement. Inadequate ergonomic conditions may result in physical discomfort and inefficient learning motivation. Environmental factors such as lighting and air quality can also influence emotional health. Given students’ ongoing interaction with their physical learning environment, this research explored how classroom ergonomics relate to academic productivity and emotional wellbeing. Using a descriptive-correlational method, the study gathered data from 179 junior and senior high school students. The results revealed that students generally rated classroom ergonomics, academic performance, and emotional well-being, including valence and activation, at high levels. Strong positive correlations were found among these variables. Notably, the comfort of classroom furniture emerged as a significant predictor, explaining 39.5% of academic productivity variance. It also predicted 26.2% of activation, while lighting conditions accounted for 30.8% of valence. The study emphasizes the importance of well-designed classrooms in promoting better academic outcomes and emotional wellbeing. Future research is encouraged to explore these dynamics using broader participant samples and considering variations across school types, age, and gender.